Electrodeposition of bilayered polypyrrole on 316 L stainless steel for corrosion prevention - González, Belén (2015)
The electropolymerization of pyrrole in aqueous solutions of salicylate leads to the formation of hollow rectangular-sectioned microtubes. With the aim to develop a coating with this morphology but with better anticorrosive properties we synthesized a bilayer system by depositing a polypyrrole underlayer electropolymerized in the presence of molybdate and nitrate and a polypyrrole film formed by the microtubes as a top layer. The corrosion performance of the coatings was monitored by following the open circuit potentials, polarization curves and electrochemical impedance spectroscopy in acid and neutral chloride solutions. The bilayers have the capacity to protect the steel against uniform as well as against pitting corrosion during long exposure times. The system with the inner layer formed in alkaline solution was the most protective coating in this study. The results are discussed in terms of the galvanic interaction between the polymer and the substrate and the role played by the dopant anions.